The Temporal Association between Body Characteristics and Speed Performance over Twenty-Five Years in Italian Adolescents - Matteo Vandoni; Vittoria Carnevale Pellino; Annalisa De Silvestri; Nicola Lovecchio; Antonio Rovida; Alessandro Gatti; Valentina Biagioli; Gianvincenzo Zuccotti; Valeria Calcaterra (MDPI AG, 2022)
Background: Physical fitness (PF) is positively related to skeletal and metabolic health, and it had an inverse relation with obesity. Adolescents with obesity have the worst performance in PF and speed-agility (SA) that contributes to an augmented risk to develop pathologies. To the best of our knowledge, many studies analyzed the trends of obesity and SA separately, but there is a lack of data about SA ability trends in adolescents with obesity. We aimed to investigate SA trends in children with obesity in the last few decades to define the association between body weight and physical performance. Methods: We recruited 3.923 Caucasian children across the period 1985-2010 in the same school in Northern Italy, near Milan. Once a year, at the ages of 11-12- and 13-years-old, we collected anthropometric measures and SA performance. We pooled the data into 5-year-period study waves and then stratified our analysis into test-sex-age BMI-z-score specific groups. Results: We reported an undetermined trend across years. The 4×5 m run test significantly decreased in adolescents with overweight/obesity, while we did not report a decline in 30 m and 60 m run tests. Conclusions: Fitness tests highlighted differences in normal weight compared to overweight/obese children, suggesting that it is crucial to carefully monitor PF capacities through the years.